“NGELEBENGANG” TRADISI PEMBUATAN GULA AREN DESA PEDAWA DALAM FOTOGRAFI STORY - Pranata, Gusti Putu Richie Efendi; Nindhia, Cokorda Istri Puspawati; Adityasmara, Farhan (Lp2mpp Isi Denpasar - Ps. Fotografi, 2021)
Palm sugar is sugar made from sap or palm tree juice. Most people prefer palm sugar because it is considered more fragrant, tasty and clean. Pedawa Village is a village that still maintains the tradition of making palm sugar known as